Glocal Radicalism: The Phenomenon of Local Islamic Radicalism in the Structure of Global Radicalism - Nani Widiawati (Islam Realitas: Journal of Islamic and Social Studies, 2020)
This article aims to reveal the dynamic factors of glocal radicalism, the tendency of superiority in the global structure, and the strategies to address the problem of glocal radicalism. Tracing the local and global context in analyzing the phenomenon of radicalism in Islam is important because both are the main variables so that this phenomenon can be comprehensively understood. This writing is qualitative research focuses on analyzing written sources about the facts of radicalism in global and local structures using analysis-interpretive methods and digital data analysis techniques. In this way, it is found that the dynamic factors of local radicalism are indirectly part of the structure of global radicalism, born of or as an implication of the systematic propaganda of that structure, namely structural violence in the dynamics and dialectics of global forces that influence social, political, and economical processes of Islamic countries. There is a tendency for superior that is reflected in the Islamophobia phenomenon and global political reflection. In this case, the moral-based multiculturalism educational approach and the virtual approach have a strategic role to address this problem Artikel ini bertujuan untuk mengungkapkan faktor dinamis radikalisme glokal, kecenderungan superioritas dalam struktur global, serta strategi untuk menyikapi problem radikalisme glokal. Penelusuran konteks lokal dan global dalam menganalisis fakta radikalisme dalam Islam menjadi penting sebab keduanya merupakan variabel utama sehingga fakta tersebut dapat dipahami secara komprehensif. Tulisan merupakan penelitian kualitatif yang memokuskan pada telaah sumber tertulis tentang fakta radikalisme dalam struktur global dan lokal dengan metode analisis-interpretatif dan teknik analisis data digital. Dengan cara demikian, ditemukan bahwa faktor dinamis radikalisme lokal secara tidak langsung menjadi bagian dari struktur radikalisme global, lahir dari atau sebagai implikasi dari propaganda sistematis dari struktur tersebut, yaitu kekerasan struktural dalam dinamika dan dialektika kekuatan-kekuatan global yang memengaruhi proses sosial, politik, dan ekonomi negara-negara Islam. Terdapat kecenderungan superiorisme yang tercermin dalam fenomena islamofobia dan refleksi politik global. Dalam hal ini, pendekatan pendidikan multikulturalisme berbasis moral serta pendekatan virtual memiliki peran strategis untuk menyikapi problem ini.